ممارسات المعلمين التدريسية في ضوء نظريات التعلم (المعرفية / جانييه/- السلوكية / ثورندايك/- الإنسانية / ماسلو/) - إبراهيم هاشم; شيبان نورا (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف البحث إلى تعرف الممارسات التدريسية لمعلمي مرحلة التعليم الأساسي /حلقة أولى/ التي يمكن أن تتم في ضوء نظريات التعلم الثلاث (جانييه- ثورندايك-ماسلو). وكذلك تعرف أثر كل من المتغيرات الآتية في الممارسات التدريسية التي يمكن أن تتم في ضوء نظريات التعلم: الجنس (ذكور– إناث)– والتخصص (رياضيات– تربية اجتماعية– علوم) – والمؤهل العلمي (معهد إعداد معلمين – إجازة جامعية – دبلوم تأهيل تربوي). وقد صممت الباحثة استبانة عن نظريات التعلم الثلاث وقد تكونت من (30) عبارة، وقُسمت إلى ثلاثة محاور حول تلك النظريات. واشتمل كل محور على عدد من العبارات الإيجابية والسلبية. وطُبقت الاستبانة على عينة عشوائية من معلمي مرحلة التعليم الأساسي /حلقة أولى/ في مدينة اللاذقية. وبلغ عدد أفراد العينة (50) معلماً ومعلمةً من تخصصات مختلفة (رياضيات– وعلوم– وتربية اجتماعية), ومؤهلات علمية مختلفة أيضاً (معهد إعداد معلمين– وإجارة جامعية –ودبلوم تأهيل تربوي). وقد توصل البحث إلى النتائج الآتية: اعتماد ممارسات المعلمين التدريسية على النظرية الإنسانية بالدرجة الأولى, فالنظرية السلوكية, فالمعرفية. عدم وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0,01) بين متوسطات إجابات المعلمين عن محاور (استخدام نظرية ثورندايك في التدريس - استخدام نظرية جانييه في التدريس- استخدام نظرية ماسلو في التدريس) تعزى لمتغير الجنس. عدم وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0,01) بين متوسطات إجابات المعلمين عن محاور (استخدام نظرية ثورندايك في التدريس - استخدام نظرية جانييه في التدريس- استخدام نظرية ماسلو في التدريس) تعزى لمتغير التخصص (رياضيات – وتربية اجتماعية – وعلوم). وجود فرق ذي دلالة إحصائية عند مستوى دلالة (0,01) بين متوسطات إجابات المعلمين عن محاور(استخدام نظرية ثورندايك في التدريس - استخدام نظرية جانييه في التدريس- استخدام نظرية ماسلو في التدريس) تعزى لمتغير المؤهل العلمي (معهد إعداد معلمين – إجازة جامعية – دبلوم تأهيل تربوي) لصالح دبلوم التأهيل التربوي. وقد قدّم البحث الحالي عدداً من التوصيات. This study aimed to know the teaching practices for teachers of basic education /cycle one/ that can be made in the light of three teaching theories (Gagne –Thorndike - Maslow), and also to know the effect of each of the following variables on the teaching practices in the light of theories of learning: sex (male- female)- Major (Mathematics- social education- science)- Qualification (Institute for the preparation of teachers– university certificate- Diploma qualification in education). The researcher designed a questionnaire about the learning theories, that consists of (30) items which are distributed to three axes about those learning theories, and each axis included a number of positive and negative items. The fact-finding had been applied on a random sample of teachers of basic education /cycle one / in Latakia city. The sample included (50) teachers from different majors (Mathematics - social education - science) and different educational qualifications (Institute for the preparation of teachers - university certificate - Diploma qualification in education). The study has given the following results: the dependence of the teaching practices of teachers on the human theory in the first grade, behavioral theory, and cognitive theory. There were no differences of statistical significance at index level (0.01) between the average responses of teachers on the questioner’s axes (using Thorndike theory in teaching - using Gagne theory in teaching - using Maslow theory in teaching) due to the variable of sex. There were no differences of statistical significance at index level (0.01) between the average responses of teachers on the questionnaire’s axes (using Thorndike theory in teaching- using Gagne theory in teaching - using Maslow theory in teaching) due to the variable of specialization (mathematics - social education - science). There were differences of statistical significance at index level (0.01) between the average responses of teachers on the questionnaire’s axes (using Thorndike theory in teaching- using Gagne theory in teaching - using Maslow theory in teaching) due to the variable of Qualification (Institute for the preparation of teachers - university certificate Diploma qualification in education) for the Diploma in Education. This study offered some Instructions.